2015
DOI: 10.1007/s11695-015-1807-3
|View full text |Cite
|
Sign up to set email alerts
|

Routine Postoperative Monitoring after Bariatric Surgery in Morbidly Obese Patients with Severe Obstructive Sleep Apnea: ICU Admission is not Necessary

Abstract: Patients with severe OSA and adequate CPAP use are at low risk of cardiopulmonary complications after (laparoscopic) bariatric surgery. Routine admission to an ICU might be superfluous. However, continuous digital oximetry remains essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Although several studies have found beneficial effects of postoperative treatment of OSA on weight loss after bariatric surgery compared to bariatric surgery alone 2830 , long-term improvement of metabolic and cardiovascular comorbidities after bariatric surgery might be linked more closely to weight loss than CPAP treatment 31,32 . During the early perioperative period, retrospective studies in patients undergoing bariatric surgery reported no differences in overall postoperative morbidity 33 , as well as no cases of death, reintubation, or cardiopulmonary complications 34,35 , regardless of CPAP or AP treatment. CPAP was found to improve blood oxygenation in patients after open Roux-en-Y gastric bypass in some studies 36 , while other authors found severe and prolonged episodes of hypoxemia during the early postoperative period despite preoperative diagnosis and treatment of OSA, including use of CPAP following bariatric surgery 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have found beneficial effects of postoperative treatment of OSA on weight loss after bariatric surgery compared to bariatric surgery alone 2830 , long-term improvement of metabolic and cardiovascular comorbidities after bariatric surgery might be linked more closely to weight loss than CPAP treatment 31,32 . During the early perioperative period, retrospective studies in patients undergoing bariatric surgery reported no differences in overall postoperative morbidity 33 , as well as no cases of death, reintubation, or cardiopulmonary complications 34,35 , regardless of CPAP or AP treatment. CPAP was found to improve blood oxygenation in patients after open Roux-en-Y gastric bypass in some studies 36 , while other authors found severe and prolonged episodes of hypoxemia during the early postoperative period despite preoperative diagnosis and treatment of OSA, including use of CPAP following bariatric surgery 37 .…”
Section: Discussionmentioning
confidence: 99%
“…RYGB had higher rates than SG or LAGB . The risk for cardiac events after bariatric surgery may be increased with OSA and this risk mitigated with the use of CPAP , though other studies fail to demonstrate these associations . Parenthetically, even though bariatric surgeries involving senior‐level residents had more statistically significant morbidities, including postoperative cardiac events, this association is more likely related to perioperative rather than intraoperative care .…”
Section: Executive Summarymentioning
confidence: 93%
“…Hence, routine preoperative clinical screening for OSA with confirmatory polysomnography may be considered, with further diagnostic testing and treatment of appropriate at‐risk patients . However, the data are generally mixed in terms of overall benefit of screening, with several studies showing no risk reduction with OSA screening or treatment .…”
Section: Executive Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…In a study involving a group of bariatric surgery patients, 30 of whom had severe OSA and were admitted in ICU for a 24-h postoperative observation, no relation between a high AHI and desaturations was found. Those findings could be explained by having one responsible nursing individual who may awaken the patients before the desaturation becomes severe (60). …”
Section: Clinical Observationsmentioning
confidence: 99%